What is alumni? / Priestly Lanting Layang ... (et al.) - Layang, Priestley Lanting; Abang Shamshudin, Dayang Nurul Amieyda; Herman, Nurul Izzah; Standard, Stephanie Sonia; Mokhtar, Muhammad Adib Azfar (Perpustakaan Tun Abdul Razak, 2023)
A person who has completed their education at a certain institution, such as high school or university, is known as an alumnus. Alumni is the plural form of the word "alumnus." This distinction is sometimes carried over from Latin into English, where it is used to refer to a female graduate as an alumna rather than alumnus. In Latin, the word alumnus refers only to male graduates. Alumnae is the correct plural form of the word "alumna." Despite this, the terms "alumnus" and "alumni" are typically utilized in a manner that is gender neutral.